AI-Driven Process Optimization in MES: Redefining Manufacturing Efficiency - Aman Jain (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Artificial Intelligence with Manufacturing Execution Systems is revolutionizing the industrial landscape, ushering in a new era of smart manufacturing. This comprehensive article explores how AI-enhanced MES transforms traditional manufacturing operations through advanced predictive maintenance, intelligent scheduling, and automated quality control. The article explores the implementation challenges, including data integration and change management, while highlighting successful case studies of smart factory transformation. By exploring the convergence of AI and MES, the article demonstrates how manufacturing facilities achieve significant improvements in operational efficiency, quality control, and resource utilization. The article also explores future directions, including edge computing integration, digital twin technologies, and cross-plant optimization, providing valuable insights for organizations planning their digital transformation journey.